Declines in the utilization of hospital‐based care during COVID‐19 pandemic. Issue 12 (29th August 2022) - Kazakova, Sophia V.; Baggs, James; Parra, Gemma; Yusuf, Hussain; Romano, Sebastian D.; Ko, Jean Y.; Harris, Aaron M.; Wolford, Hannah; Rose, Ashley; Reddy, Sujan C.; Jernigan, John A.
Abstract: The disruptions of the coronavirus disease 2019 (COVID‐19) pandemic impacted the delivery and utilization of healthcare services with potential long‐term implications for population health and the hospital workforce. Using electronic health record data from over 700 US acute care hospitals, we documented changes in admissions to hospital service areas (inpatient, observation, emergency room [ER], and same‐day surgery) during 2019−2020 and examined whether surges of COVID‐19 hospitalizations corresponded with increased inpatient disease severity and death rate. We found that in 2020, hospitalizations declined by 50% in April, with greatest declines occurring in same‐day surgery (−73%). The youngest patients (0−17) experienced largest declines in ER, observation, and same‐day surgery admissions; inpatient admissions declined the most among the oldest patients (65+). Infectious disease admissions increased by 52%. The monthly measures of inpatient case mix index, length of stay, and non‐COVID death rate were higher in all months in 2020 compared with respective months in 2019.